Chemical treatment of wheat straw on intake and nutrient utilization in sheep - SAHOO, B; SARASWAT, M L; HAQUE, N; KHAN, M Y (The Indian Journal of Animal Sciences, 2014)
Muzaffarnagari sheep randomly assigned to 3 groups of 5 animals each were used to study the effect of chemically treated wheat straw on nutrient utilization. Wheat straw was treated either with urea (4 kg urea/ 100 kg DM) with a storage time of 21 days (treatment 1 control) or urea supplementation (1.5 kg/ 100 kg DM) without storage time (treatment 2) or urea plus calcium hydroxide (3 kg urea plus 3 kg calcium hydroxide/100 kg DM ) with a storage time of 21 days (treatment 3). All the animals were allowed to fed respective diet ad lib. The crude protein (CP) content of wheat straw during feeding was 7.8%, 7.9% and 7.6% in treatments 1,2 and 3, respectively. Corresponding dry matter (DM) intake was 50.7.37.8 and 52,7 g/kg W0.75/day, respectively. which was higher (P<0.05) in treatments 1 and 3 than that of treatment 2. The DM digestibility in treatments 1.(49.8%) and 3 (47.9%) was higher (P<0.05) than that of treatment 2 (42 6%). The digestibility of cellulose and ADF also followed similar trend. The CP digestibility, was similar in all the 3 groups whereas, OM, NDF and hemicellulose digestibility were highest (P<0.05) in group 1 and lowest in group 2. Animals in all the 3 groups were in positive nitrogen balance (g/day) while it was higher (P<0.01) in group 3 (2 g/days) than in group 1 (0.94 g/day) and group 2 (0.50 g/day). The DCP intake was similar in all the 3 groups while the TDN intake in treatments 1 and 3 was higher (p<0.01) than treatment 2. The calculated DCP and TDN values assessed in terms of percentages were 2.70. 2.96 and 2.50; 50.7, 39.8, and 43.5 in treatments 1,2 and 3, respectively. It is concluded that treatment of wheat straw with urea andlor a mixture of urea with calcium hydroxide followed by storage can improve nutrient digestibility compared to spraying with urea solution prior to feeding, Addition of urea with calcium hydroxide increased the retention of N in animal body than urea-ammoniation of wheat straW alone.